PENGARUH KUALITAS KEHIDUPAN KERJA, BUDAYA ORGANISASI DAN KEPEMIMPINAN MELAYANI TERHADAP KEPUASAN KERJA STUDI PADA RUMAH SAKIT ISLAM KABUPATEN KENDAL - Ahmad Ashifuddin Aqham, 1342020044 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine the effect of the quality of work life, culture organizational and leadership serves on job satisfaction on employee and hospital of medical Islam Kendal. The population in this study were all employees of the medical part and supporting part of the hospital of medical Islam Kendal district. The sample in this study of 115 respondents using purposive sampling method. The analysis tool used is multiple linear regression analysis were first tested the validity and reliability. From the results of regression analysis shows that the quality of work life and make positive significant effect on job satisfaction, culture organizational make positive significant impact on job satisfaction and leadership serves positive significant impact on job satisfaction. Keywords: quality of work life, culture organizational, leadership serves, job satisfaction,